The Role of Brand Image Mediation in the Influence of Price and Promotion on Students' Decisions in Choosing Private Universities - Yusuf, Yusuf Tojiri (Jurnal Economic Resource, 2025)
Competition among higher education institutions in Indonesia is increasing, requiring educational institutions to not only maintain academic quality but also optimise non-academic strategies such as pricing, promotion, and brand image. This is important because changes in student consumer behaviour increasingly emphasise affordability, promotional effectiveness, and positive perceptions of institutions. This study aims to analyse the influence of price and promotion on students' decisions in choosing a higher education institution, with brand image as a mediating variable. This study employs a quantitative approach with an explanatory research design. The study population consists of active students who are at least in their second semester and prospective new students at a private higher education institution. The sampling technique employed is purposive sampling, involving a total of 200 respondents. Data were collected through a Likert scale-based questionnaire and supplemented with secondary data, including institutional documents and relevant literature. Data analysis used the Structural Equation Modelling–Partial Least Squares (SEM–PLS) method. The results showed that price and promotion had a positive effect on brand image and student decisions. In contrast, brand image played an important role both directly and as a partial mediator. These findings confirm that students' decisions in choosing a university are influenced not only by cost and promotion, but also by the positive image that the institution projects. The implication of this study is the need for universities to design transparent pricing strategies, create and implement creative and relevant promotions, and strengthen their image through academic quality and sustainable services.